Connecting music and art through music technology - Hade, Rebekah A. (Kansas State University, 2021)
The lessons included in this report concentrate on the relationship between music and art and the expressiveness of musical improvisation and approximation. These lessons incorporate Wassily Kandinsky’s approach to using music to create works of art and utilizing music technology to create a soundscape inspired by feelings, objects, and artistic creations. The activities presented in this report were developed from the growing need for students to be fluent in their knowledge of Digital Audio Workstations such as GarageBand and Soundtrap. Prior to this unit, students had a general understanding of modern band instruments like guitar, bass, keyboard, and drums. What was needed was a way to record their work and distribute it publicly. These lessons provided a way for students to begin their journey in discovering ways to use technology to create music. The Kandinsky unit taught in the following lessons was inspired by a newfound love for teaching improvisation to students. During my time in the Masters’ Program, I learned that improvisation in the classroom is wonderful when embraced by both the teacher and the students. I found that using multimedia techniques, such as art, instrumental performance, and music technology, make teaching improvisation less intimidating and more captivating. Using the methodologies taught in the Graduate Program have also informed my teaching in a transformative way. Using play and personal expression inspired by Orff and Gordon, my teaching has become more diverse and rewarding in ways that even my students have come to recognize. This growth in my teaching has led me to the unit presented in this report and I am looking forward to future developments as an educator that will allow me to build on the foundation provided from this program.
Keywords: Kandinsky; Music technology; Music composition